Knowledge Management System Knowledge Management System Informasi dan Pemesanan Makanan Pada Bakmi Golek Rawamangun - geren widya agasti; puput irfansyah M.Kom; eko harli M.Kom (Sekolah Tinggi Teknik - PLN, 2021)
Bakmi Golek is a restaurant that has been around for a long time and not only provides noodles but other Chinese food. The ordering system at Bakmi Golek Rawamangun still uses a manually, so the customer assess there are still several problems, including the food ordering process still using handwriting. The data storages are still using paper media, data search will take a long time because it must have to find a paper one by one on an archive, and making reports still require a lot of writing, so the data that has been stored in the archive will be lost. The purpose of this research is to provide effective and efficient solutions through KMS to Bakmi Golek Rawamangun employees in order to help improve performance while doing work, make KMS on there, to facilitate users in carrying out buying and selling transactions, data processing and checking sales reports and for presents a good ordering system by providing convenience and information for consumers in the food ordering process. The method used in this study is a research and development method with system development using the waterfall method. The result of this research is an application system of order and food information based on knowledge management system.